METHOD AND SYSTEM FOR A VOICE ASSISTED QUALITY INSPECTION - SHARMA, HIMANSHU; VISHWAKARMA, ARPIT; MALHOTRA, CHETAN PREMKUMAR; BASAVARSU, PURUSHOTTHAM GAUTHAM (2025)
The embodiments of present disclosure herein address unresolved problems of handwritten notes or digital diaries for logging defects during quality inspection. Also, these kinds of inspections in the industries are time bound. In certain sensitive inspection cases inspectors are required to use gloves while inspecting which leads to added overhead of working with gloves while noting down the defects. Sharing of these defect logs also becomes difficult as they first must be digitized to be shared across the different units in the industry. Embodiments herein provide a method and system which logs the defects identified by inspectors using inspector's voice. The system identifies defect type, location and sub-section from inspector speech and marks the defect in an orthogonal view, a two-dimensional (2D) view, a three-dimensional (3D) view of the artifact being inspected for verification. The system also allows for marking the defects as resolved during the repair or rework process.